Correlation Between Central Corneal Thickness and Intraocular Pressure with the Goldmann Applanation Tonometer - Alshehri, Fayez; Alrashidi, Badriah (American Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: The aim of this review is to investigate the correlation between central corneal thickness (CCT) and Intraocular pressure with the Goldmann applanation tonometer (GAT). Materials and Methods: A literature search using Medline database was conducted for the years 1946 to 2022 to explore the relationship between central corneal thickness and Intraocular pressure measured by the Goldmann applanation tonometer. The search was restricted to studies published in English language. The first 80 articles were reviewed and five relevant studies were selected in this analysis. Findings: Impacts of central corneal thickness on Intraocular pressure were investigated in five studies. Overestimation of intraocular pressure is associated with thick cornea while underestimation of intraocular pressure was associated with thin cornea Implications to Theory, Practice and Policy: Central corneal thickness can affect the result of Intraocular pressure measurement with the Goldmann applanation tonometer (GAT) . Assessment of central corneal thickness (CCT) is necessary for correct interpretation of IOP measurements obtained with the Goldmann applanation tonometer (GAT).